Tight Blood-Glucose Control without Early Parenteral Nutrition in the ICU - Gunst, Jan; Debaveye, Yves; Güiza, Fabian; Dubois, Jasperina; De Bruyn, Astrid; Dauwe, Dieter; De Troy, Erwin; Casaer, Michael P.; De Vlieger, Greet; Haghedooren, Renata; Jacobs, Bart; Meyfroidt, Geert; et al. (The New England journal of medicine, 2023)
In this randomized, controlled trial involving critically ill patients not receiving early parenteral nutrition, tight glucose control did not affect the length of time that ICU care was needed or mortality.